Secuencias didácticas para la enseñanza de la geología económica: una reflexión crítica (2000)
An alternative methodological framework to the traditional teaching of economic geology is proposed. We intend to give an answer to the didactic dificulties with respect to the leaming of economic geology. Geoscience education to future mining engineers has to be thought in this sense with three aims: (1) showing to future citizens the nature of geoscience; (2) beginning to teach to future scientists how to do geoscience; (3) teaching to students some features of the natural world.